Asuhan Kebidanan Neonatus Pada Bayi Di Puskesmas Bontobangun Kecamatan Rilau Ale Kabupaten Bulukumba Tahun 2023 - Eka Juniali, Sri; Tenri Fada, Besse; Wiriyanti, Murida (Universitas Sumatera Barat, 2023)
Neonates are a normal process, but this condition can turn abnormal if supervision is not carried out. Complications that can occur are one of the causes of irregular neonatal visits. So comprehensive midwifery care is needed, where this care is expected to be able to minimize complications that can occur in neonates. The aim is to provide comprehensive care for NY